Eales' Disease - A Distressing Mystery - Ishaq, Brigadier Mazhar (Pakistan Journal of Ophthalmology, 2011)
Eales’ disease is an idiopathic; occlusive periphlebitis affecting the peripheral retina of young healthy males. Retinal changes are characterized by perivasculitis, peripheral ischemia and neovascularization leading to recurrent vitreous hemorrhage and other sequelae. In 1880, Henry Eales – a British Ophthalmologist first observed the disease entity characterized by idiopathic vitreous hemorrhage in young males. He observed seven males of ages 14 – 29 years, all of them having history of headache, epistaxis and constipation1. The disease was considered to be vasomotor neuritis till five years later Wardsworth explained its association with retinal inflammation2. Though cases of Eales’ disease have been reported in Europe and North America but for unknown reasons it is rare in the developed world and more commonly reported in the Indian Subcontinent. Its incidence in India is 1 in every 200 – 250 ophthalmic patients. Eales’ disease targets healthy young adults, mostly males (Male predominance is up to 97.6%3,4) with an age group ranging from 20 – 30 years. The disease is bilateral 50–90% of the time5,6 and thus causes significant socioeconomic burden.